Is Local Beautiful? Peacebuilding between International Interventions and Locally Led Initiatives - Hellmüller, Sara; Santschi, Martina (Peace and Security Studies ;, 2014)
Based on the swisspeace annual conference 2012, the publication examines the delicate balance between external interventions and locally-led initiatives. It addresses the question of what "local" means in the peacebuilding and development context; which actors on the ground actually represent the local level and how external actors choose their partners from amongst them. Moreover, it examines how local ownership - emerging as key criteria for any external intervention - is constituted: does this concept only imply local participation or is local control from the outset a must? Finally, it assesses the potential of locally-led initiatives and local conflict resolution mechanisms and their interaction with external interventions. Several authors provide insights on these questions and nuance our thinking about both local ownership and external interventions. As such, the publication aims to encourage critical reflections on this topical debate in peacebuilding and development.